(3JMaI GdMcjes - (3GdCUagGfj, GdCUagGfj, eMeO MSjf Hf eMeO MSf eYjf GdJLGQ, J (B1361(3g` (B1942(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3JYQja GdhLhO, GdMO cGdQSe Ydi GdJMbjb (B*** (3jhUa HGdG Sej hGdMbjbj (B*** (3hdG jbGd aj LhGH GdTGQMI (B*** (3EdG MOhO Ch QShe TGQMIs
(3BNQgG (B:s
(3BNQgG(B: (3hChd GdeQGJH GdYbdjI (B*** (3gj GdMbjbI GdeMeOjI (B*** (3ZeG RYGg bdHg eeG hYG (B*** (3gd jchf bQGfG haQbGfG eYGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 106s
(3GdPQjYI, L (B3: 235s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs